Morphological and pathogenic characterization of Fusarium oxysporum f. sp. ciceri causing wilt of chickpea - and J. AKHTAR, ATUL KUMAR*, H.C. LAL (Indian Phytopathology, 2012)
An extensive survey was conducted during 2007-09 in the Eastern plateau region to study morphological and pathogenic variability amongst isolates of wilt pathogen. Diseased samples from twelve districts were collected and isolations were made from roots of wilted plants. The disease was prevalent at all the locations surveyed and the disease incidence varied from 38.7 to 59.2%. Twenty four isolates were collected of which , four isolates of Fusarium oxysporum f sp ciceri from Ranchi, Dumka, Darisai and Chatra were selected for variability studies being geographically distantly located and showing maximum wilt incidence. Terminal Chlamydospores were seen in Chatra isolate which differentiates it from others which were having intercalary Chlamydospores. Maximum sporulation of 1.0x 106 conidia /ml was seen in Ranchi Isolate and minimum of 0.4x106 conidia /ml was observed in Dumka Isolate. On International set of Chickpea differentials, Isolates from Ranchi Dumka and Darisai showed reaction similar to race 7 while Chatra isolate showed reaction similar to race 4 which is a new race report from the state.